2013
DOI: 10.15288/jsad.2013.74.674
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fathers’ Alcohol Problems on the Development of Effortful Control in Early Adolescence

Abstract: This article examines the association between fathers' alcohol problems and children's effortful control during the transition from middle childhood to early adolescence (fourth to sixth grade). Additionally, we examined the role of two potential moderators of this association, fathers' antisocial behavior and child gender. Method: The sample consisted of 197 families (102 nonalcoholic [NA]; 95 father alcoholic [FA], in which only the father met diagnostic criteria for alcohol abuse or dependence). The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…In contrast, there were no significant associations between maternal substance use disorder or parenting stress and child effortful control or externalizing behaviors. Previous research has found associations between reduced effortful control in the child and greater externalizing problems in early childhood (Eiden et al, ) and adolescence (Adkison et al, ) in children of parents with substance use disorders. The lack of these associations may be due to a number of reasons.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, there were no significant associations between maternal substance use disorder or parenting stress and child effortful control or externalizing behaviors. Previous research has found associations between reduced effortful control in the child and greater externalizing problems in early childhood (Eiden et al, ) and adolescence (Adkison et al, ) in children of parents with substance use disorders. The lack of these associations may be due to a number of reasons.…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, the present study only examined the effect of mothers on child outcomes. Children's relationships with their fathers are important as past literature has shown (Adkison et al, ; Eiden et al, ). Fathers may have unique effects on children's effortful control or interactive effects with maternal characteristics, which should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children of substance abusers were found to be more likely to consume and face substance use related problems (Buu et al, 2012). Moreover, these individuals tends to start the consumption of alcohol and drugs earlier, when compared to children of non-addicts and, in early adolescence, have significantly higher odds of drinking alcohol, using illicit drugs, drinking heavier, and presenting addiction symptoms (Adkison et al, 2013).…”
mentioning
confidence: 99%